PENINGKATAN PREFERENSI KONSUMEN TERHADAP PRODUK BERLABEL HIJAU MELALUI SIKAP, KUALITAS PRODUK, DAN TINGKAT PENDIDIKAN DALAM KONTEKS IKLAN MEREK HIJAU - Suhartina Suhartina (Jurnal Riset Bisnis Indonesia, 2015)
This study aimed to describe and analyze the relationship of some variables which consist of greenbrand products quality, the level of education, attitude towards products, and consumer green brandpreferences in choosing green brand products. This study also aimed to develop a model of greenbrand advertising role in moderating the equation of consumers’ green brand preferences. Thepopulations in this study are all consumers of Bio Sanitary Pad Avail which purchase the produk atthe authorized agency of Avail Elok Jakarta, Semarang branch. Convenient sampling approach byusing Wibisono formula is used to determine the amount of sample (sample size) which obtained thetotal sample of 100 respondents. Sampling taking was done by purposive random sampling methods.The chosen samples are given questionnaires and then later analized by using Structural EquationModeling (SEM) with the method of Partial Least Square (PLS). The results showed that the level ofeducation has significant effect on the preference of green-labeled products, the level of educationhas a significant effect on consumer attitudes on environmentally friendly products, product qualityhas significant effect on the green-labeled product preferences, attitudes on green products hassignificant effect on their preferences in buying a green label products. While product quality has nosignificat effect on costumer attitude. Green brand advertising as a moderating variable can providea moderating effect on the equation which result the increasing of consumer preference towardsgreen products as proposed by researchers.Keywords: green brand product quality, level of education, attitude to the product, the green brandadvertising, consumer green preferences.